Viability of fresh aortic valve homografts: a quantitative assessment. Issue 1 (January 1972) - Al-Janabi, N.; Gonzalez-Lavin, L.; Neirotti, R.; Ross, D. N.
Abstract : Accumulated evidence indicates that fresh aortic valve homografts function longer than preserved grafts. Thus it becomes important to assess the viability of fresh homografts on a quantitative basis. Recently, we have used autoradiography in addition to tissue culture to determine the viability of fresh aortic and pulmonary valve homografts. The uptake of thymidine was gradually reduced to 50% after 18 days of preservation in a balanced salt solution with antibiotics and the uptake was reduced to 21% in 63 days. We think that a nutrient medium is necessary if longer viability is to be obtained.